Differential effects of interpersonal relationships across functions on product and service innovation. Issue 5 (23rd March 2021) - Wang, Feng; Cao, Rong; Wu, Siting; Chen, Man
Abstract : Purpose: The aim of the study was to investigate the differential effects of interpersonal relationships across functions on product and service innovation, and to examine the moderating role of market competition. Design/methodology/approach: This study was based on a survey of senior and middle managers from 149 pharmaceutical firms in China. Findings: Interpersonal relationships between employees across functions (IR-E) have a stronger impact on product innovation than do interpersonal relationships between managers across functions (IR-M), but IR-M have a stronger impact on service innovation. Market competition strengthens the effects of IR-M on both product and service innovation, but it attenuates the effect of IR-E on service innovation. Originality/value: Although the effects of interpersonal relationships across functions are crucial to cross-functional interactions, these effects have received little attention in the literature. By identifying the potential "backfiring" effect of dual-level interpersonal relationships, this study contributes to knowledge of cross-functional relationships. It also deepens understanding of the relationship between cross-functional relationships and organizational innovation, especially in the service setting.